PSXIII-30 Analysis of gene expression profiles in liver and muscle tissue of pigs divergent in feed efficiency - Vigors, Stafford (J Anim Sci, 2019)
The improvement of feed efficiency is a key economic goal within the pig production industry. The objective of this study was to examine transcriptomic differences in both the liver and muscle in pigs divergent for feed efficiency, thus improving our understanding of the molecular mechanisms influencing feed efficiency and enabling the identification of candidate biomarkers. Residual feed intake (RFI) was calculated in two populations of pigs from two different farms of origin. The 6 most efficient (LRFI) and 6 least efficient (HRFI) animals in each population were selected for further analysis of Longissimus Dorsi muscle and liver. Three different analysis were performed: 1) Identification of differentially expressed genes (DE) in liver, 2) Identification of DE genes in muscle and 3) Identification of genes commonly DE in both tissues. Hierarchical clustering revealed that transcriptomic data segregated based on the RFI value of the pig rather than farm of origin. A total of 6464 genes were identified as being differentially expressed (DE) in muscle, while 964 genes were identified as being DE in liver. In the muscle-only analysis, genes associated with RNA, protein synthesis and energy metabolism were downregulated in the LRFI animals while in the liver-only analysis, genes associated with cell signalling and lipid homeostasis were upregulated in the LRFI animals. Genes that were commonly DE between muscle and liver (n = 526) were used for the joint analysis. These 526 genes were associated with protein targeting to membrane, extracellular matrix organization and immune function. There are pathways common to both muscle and liver in particular genes associated with immune function. In contrast, tissue-specific pathways contributing to differences in feed efficiency were also identified with genes associated with energy metabolism identified in muscle and lipid metabolism in liver. This study identifies key mechanisms driving changes in feed efficiency in pigs.